2013
DOI: 10.1080/02786826.2012.716174
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigations of the Effect of the Calibration Aerosol Material on the Counting Efficiencies of TSI 3790 Condensation Particle Counters

Abstract: The counting efficiencies of two TSI 3790 Condensation Particle Counters (CPCs) were investigated experimentally for graphite, poly-(alpha)-olefin (PAO), tetradecane (C14), and hexadecane (C16) particles at saturator-to-condenser temperature differences spanning from 5.6• C to 11.3 • C. The efficiencies determined with PAO, C14, and C16 particles were broadly similar, while tests with graphite particles resulted in systematically lower counting efficiencies. The differences between PAO and graphite particles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…This evidence raises concerns regarding the traceability of CPC calibrations against combustion aerosol. On the other hand, the counting efficiencies for emery oil, while not representative of combustion soot, reproduced the manufacturer's certified values to within 4%, in good agreement with other published data (Giechaskiel and Bergmann 2011;Mamakos et al 2013).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This evidence raises concerns regarding the traceability of CPC calibrations against combustion aerosol. On the other hand, the counting efficiencies for emery oil, while not representative of combustion soot, reproduced the manufacturer's certified values to within 4%, in good agreement with other published data (Giechaskiel and Bergmann 2011;Mamakos et al 2013).…”
Section: Discussionsupporting
confidence: 78%
“…The certification values by TSI, determined using emery oil, are also shown (crosses). primary particle sizes pointing towards a morphology effect on the activation energy barrier (i.e., affecting the contact line Mamakos et al 2013). Differences in the chemistry of the particle surface and/or adsorbed volatile material could also have contributed to the different affinity for butanol.…”
Section: Affinity For Butanolmentioning
confidence: 99%
See 1 more Smart Citation
“…The different residence times, the different dilutions (10 versus 1000), and the different operating temperatures of the detectors (60 • C versus 25 • C) of the PEMS10 and TP10 respectively are also expected to have affected the size of these particles. It is also possible that the lower 23 nm measurements with the reference system at the tailpipe is linked to the lower affinity of these particle for butanol [59,60]. Table 1.…”
Section: Nucleation Mode Particlesmentioning
confidence: 99%
“…Several authors found a strong dependence on the chemical composition of the calibration material used for the 50% cutoff diameter determination (Wang et al 2010;Mamakos et al 2013). Furthermore, a degradation of the performance of the CPCs after extended use was noticed .…”
Section: Introductionmentioning
confidence: 99%